The cultural diversity as pedagogical power: from the meeting to the intercultural education - Silva, Ana TerezaReis da (2021)
In this article, we analyze the cultural diversity and intercultural encounters that take place at the school Escola Classe Sítio das Araucárias, located in Rota do Cavalo, Sobradinho-DF. The empirical research that informs the article was carried out throughout 2019 by means of interviews and rounds of conversation with the School's teaching staff and by means of participant observation with families living in the region, in their collective spaces and territories of experiences. Based on these two methodological procedures, we analyze the cultural diversity that constitutes the Horse Route and the ways in which it has been, at the same time, affirmed, denied, marked and shared in the school context. Based on this, we analyze the pedagogical challenges that arise from living with difference, as well as indicate some potentials that the intercultural encounter points out with a view to building a critically oriented intercultural education.